2015
DOI: 10.1111/eos.12224
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation with periodic alternating intervals stimulates neuronal cells to produce neurotrophins and cytokines through activation of mitogen‐activated protein kinase pathways

Abstract: Peripheral neuropathy is a representative complication of dental surgery. Electrical therapy, based on electrical stimulation with periodic alternating intervals (ES-PAI), may promote nerve regeneration after peripheral nerve injury in a non-invasive manner, potentially providing an effective therapy for neuropathy. This study aimed to analyze the molecular mechanisms underlying the nerve recovery stimulated by ES-PAI. In brief, ES-PAI was applied to a neuronal cell line, Neuro2A, at various intensities using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Consistent with our findings, other studies also reported that MS induces the expression of RANKL via p38 in osteoblasts derived from alveolar bone and that electrical stimulation increases the level of phosphor-p38 and ERK1/2 in nerve cells (Yamamoto et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, other studies also reported that MS induces the expression of RANKL via p38 in osteoblasts derived from alveolar bone and that electrical stimulation increases the level of phosphor-p38 and ERK1/2 in nerve cells (Yamamoto et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Further, DC-induced activation of the PI3K/AKT pathway was also reported in different cell types, including neural progenitor cells [47], Schwann cells [48], and human umbilical vein endothelial cells (HUVEC) [49], as well as in ocular cells, including the corneal epithelium [6,50]. Activation of the MAPK signaling pathway is also reported through the application of EFs in neuronal cells [51,52], fibroblasts, HUVEC [53], and corneal epithelial cells [6]. Likewise, we also observed activation of PI3K/AKT and MAPK signaling pathways, along with other interconnected pathways, including T cell receptor signaling, Toll-like receptor signaling, TNF signaling, IL-17 signaling, FoxO signaling, and focal adhesion pathways, upon stimulation of corneal epithelial cells with oscillating EFs.…”
Section: Discussionmentioning
confidence: 88%
“…Animal RCTs were included to examine other independent variables that have not yet been analyzed in humans. A total of 52 articles were selected for inclusion, with 45 studies [ 8 , 11 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] on mechanisms and seven RCTs [ 73 , 74 , 75 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%